2008
DOI: 10.2746/042516408x320898
|View full text |Cite
|
Sign up to set email alerts
|

The use of race winnings, ratings and a performance index to assess the effect of thermocautery of the soft palate for treatment of horses with suspected intermittent dorsal displacement. A case‐control study in 110 racing Thoroughbreds

Abstract: Production of a reliable measure of racehorse performance may be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 20 publications
1
37
1
Order By: Relevance
“…Three studies have previously performed comparative work to assess the ability of outcome measures to represent racing success [2,4,20]. Reardon et al [4] compared the use of median Racing Post Rating earnings and points for first to third (as defined by Woodie et al [31]) for three races before and after surgical intervention for a chronic upper respiratory tract disorder. Cheetham et al [20] investigated whether both race earnings and number of race starts were associated with horse signalment (age, sex and breed), gait and race surface for TBs and SBs in North America, concluding that studies should report both measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies have previously performed comparative work to assess the ability of outcome measures to represent racing success [2,4,20]. Reardon et al [4] compared the use of median Racing Post Rating earnings and points for first to third (as defined by Woodie et al [31]) for three races before and after surgical intervention for a chronic upper respiratory tract disorder. Cheetham et al [20] investigated whether both race earnings and number of race starts were associated with horse signalment (age, sex and breed), gait and race surface for TBs and SBs in North America, concluding that studies should report both measures.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their relatively high value within the equine industry, racehorses are often subjected to diagnostic and therapeutic interventions and provide a unique population for which objective performance measurements are available for each participating individual in the form of racing outcome. However, there remains no consensus on what objective measures quantify racehorse performance appropriately [3,4], and debate continues as to what measures may represent 'success' more meaningfully; a measure of 'longevity', such as ability to continue racing over an extended time frame, or a measure of 'quality', such as the ability to win a top rated race or accrue earnings [5]. However, there remains no consensus on what objective measures quantify racehorse performance appropriately [3,4], and debate continues as to what measures may represent 'success' more meaningfully; a measure of 'longevity', such as ability to continue racing over an extended time frame, or a measure of 'quality', such as the ability to win a top rated race or accrue earnings [5].…”
Section: Introductionmentioning
confidence: 99%
“…) and one was level 2 (cohort study using racing peers; Reardon et al . ). Additionally, there is a systematic review of all these studies authored by Allen et al .…”
Section: Quantity and Quality Of Studiesmentioning
confidence: 97%
“…Five studies were identified that investigated the effects of thermocautery of the soft palate (Ordidge ; Reardon et al . ; Barakzai et al . ; Franklin et al .…”
Section: Quantity and Quality Of Studiesmentioning
confidence: 99%
“…Additionally, there has been new information that continues to build a body of evidence against use of staphylectomy and various forms of palatoplasty for most horses with this condition. 5,[31][32][33] There is increasing support implicating laryngohyoid positioning as a factor associated with DDSP. 5,6,9,20,21,24,34 As such currently the most widely accepted surgical intervention, following failed conservative therapy, is laryngeal tie-forward with or without myectomy of the sternohyoideus and sternothyrohyoideus.…”
Section: Update On Diseases and Treatment Of The Pharynxmentioning
confidence: 98%